Evaluation of Decellularized Extracellular Matrix of Skeletal Muscle for Tissue Engineering. Issue 7 (July 2014) - Lin, Chih-Hsun; Yang, Jenn-Rong; Chiang, Nai-Jung; Ma, Hsu; Tsay, Ruey-Yug
Objective: We evaluated the effectiveness of enzyme-detergent methods on cell removal of mouse skeletal muscle tissue and assessed the biocompatibility of the decellularized tissues by an animal model. Methods: The mouse latissimus dorsi (LD) muscles underwent decellularization with different enzyme-detergent mixtures (trypsin-Triton X-100, trypsin-sodium dodecyl sulfate (SDS), trypsin-Triton X-100-SDS). The effectiveness of decellularization was assessed by histology and DNA assay. The content in collagen and glycosaminoglycan was measured. The biomechanical property was evaluated in uniaxial tensile tests. For biocompatibility, the decellularized muscle specimens were implanted in situ and the tissue samples were retrieved at day 10, 20, and 30, to evaluate the host-graft inflammatory reaction. Results: Extensive washing of the mouse LD muscles with an enzyme-detergent mixture (trypsin and Triton X-100) can yield an intact matrix devoid of cells, depleted of more than 93% nuclear component and exhibiting comparable biomechanical properties with native tissue. In addition, we observed increased infiltration of inflammatory cells into the scaffold initially, and the presence of M1 (CD68)-phenotype mononuclear cells 10 days after implantation, which decreased gradually until day 30. Conclusions: The enzyme-detergent method can serve as an effective method for cell removal of mouse skeletal muscle. In short-term follow-up, the implanted scaffolds revealed mild inflammation with fibrotic tissue formation. The decellularized extracelluar matrix developed herein is shown to be feasible for further long-term study for detailed information about muscle regeneration, innervation, and angiogenesis in vivo.